ARTIFICIAL INTELLIGENCE: CURRENT STATE, CHALLENGES, AND FUTURE PROSPECTS (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
Artificial intelligence (AI) has rapidly evolved from a narrow field of academic research into a transformative technology shaping modern science, the economy, and education. This article examines contemporary approaches to the development of intelligent systems, key application domains of AI, and the major ethical, social, and technological challenges faced by the global community. Particular attention is given to the prospects for AI development and its role in shaping a data-driven digital future, with a specific focus on education and learning analytics.
Keywords: Artificial intelligence, machine learning, neural networks, digital transformation, AI ethics, education.